Smart Sensing and Context 5th European Conference, EuroSSC 2010, Passau, Germany, November 14-16, 2010. Proceedings - Lukowicz, Paul.; Kunze, Kai.; Kortuem, Gerd.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the revised papers of the 5th European Conference on Smart Sensing and Context, EuroSSC 2010, held in Passau, Germany, in November 2010. The 13 revised full papers were carefully reviewed and selected from numerous submissions. The papers address topics such as applications; sensing; systems support; and higher level modeling. In addition to the Conference is a short report about the Workshop on Ambient Assisted Living (AAL) Platform included.
Applications -- FireGuide: A Context-Aware Fire Response Guide for the Building Occupants -- How to Log Sleeping Trends? A Case Study on the Long-Term Capturing of User Data -- Utilizing Social Context for Providing Personalized Services to Mobile Users -- Sensing -- Activity Recognition Using Biomechanical Model Based Pose Estimation -- Energy Efficient Cooperative Multimodal Ambient Monitoring -- On the Use of Magnetic Field Disturbances as Features for Activity Recognition with on Body Sensors -- Systems Support -- Feature Weighting for CPM-Based Context Validation -- A Formal Model of Reliable Sensor Perception -- Effect of Caching in a Broker Based Context Provisioning System -- A Logic Based Context Query Language -- Higher Level Modeling -- Sensor Abstractions for Opportunistic Activity and Context Recognition Systems -- Identifying Important Action Primitives for High Level Activity Recognition -- A Resource Model for the Real World Internet -- Report on the Workshop on ICT and Ageing: Announcing the European Initiative for an Ambient Assitant Living (AAL) Platform -- Platforms for AAL Applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information systems; Computer Science; Information Systems Applications (incl.Internet).; Computer Communication Networks; Special Purpose and Application-Based Systems; User Interfaces and Human Computer Interaction; Software Engineering; Computers and Society